The Use of Gamification in Teaching and Learning Mathematics: A Meta-Synthesis - Angco, Robert Jay Naigar (Jurnal Pendidikan Progresif, 2023)
The Use of Gamification in Teaching and Learning Mathematics: A Meta-Synthesis. Objectives: This study aimed to explore and synthesize the use of gamification in teaching and learning mathematics. Methods: A meta-synthesis was used in this systematic review to focus on the use of gamification in teaching and learning mathematics. The final 13 articles in this study were developed using the Critical Appraisal Skills Programme (CASP) checklist and structured using the PRISMA 2020 flow diagram. Findings: Four themes emerged from the thematic analysis, namely: time element, positive attitude, collaboration and engagement, and feedback and assessment. A meta-theme emerged as Futures Thinking: Gamifying Mathematics Education for Engaged Learning. Conclusion: The findings provide significant insights for educators and curriculum designers looking for novel techniques to improve mathematics teaching and learning. It should be noted that the effectiveness of gamification in mathematics teaching and learning is dependent on the careful design and implementation of the gamified features. Clear learning objectives, adequate feedback methods, and a balance of challenge and support are all critical considerations. Keywords: Gamification, meta-synthesis, systematic review, teaching mathematicsDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202304